Chimerism, Graft Survival, and Withdrawal of Immunosuppressive Drugs in HLA Matched and Mismatched Patients After Living Donor Kidney and Hematopoietic Cell Transplantation. Issue 3 (March 2015) - Scandling, J. D.; Busque, S.; Shizuru, J. A.; Lowsky, R.; Hoppe, R.; Dejbakhsh‐Jones, S.; Jensen, K.; Shori, A.; Strober, J. A.; Lavori, P.; Turnbull, B. B.; Engleman, E. G.; et al.
Abstract Thirty‐eight HLA matched and mismatched patients given combined living donor kidney and enriched CD34+ hematopoietic cell transplants were enrolled in tolerance protocols using posttransplant conditioning with total lymphoid irradiation and anti‐thymocyte globulin. Persistent chimerism for at least 6 months was associated with successful complete withdrawal of immunosuppressive drugs in 16 of 22 matched patients without rejection episodes or kidney disease recurrence with up to 5 years follow up thereafter. One patient is in the midst of withdrawal and five are on maintenance drugs. Persistent mixed chimerism was achieved in some haplotype matched patients for at least 12 months by increasing the dose of T cells and CD34+ cells infused as compared to matched recipients in a dose escalation study. Success of drug withdrawal in chimeric mismatched patients remains to be determined. None of the 38 patients had kidney graft loss or graft versus host disease with up to 14 years of observation. In conclusion, complete immunosuppressive drug withdrawal could be achieved thus far with the tolerance induction regimen in HLA matched patients with uniform long‐term graft survival in all patients.